The Influence of Lifestyle and Digital Marketing on the Facebook Platform on Purchase Decisions in the Used Car Business in Lampung - Refflin, William; Alam, Iskandar Ali (LPPPIPublishing, 2025)
The purpose of this research is to analyze the influence of lifestyle and digital marketing on the Facebook platform on purchasing decisions in the used car buying and selling business in Lampung. This study uses a quantitative method by collecting data through questionnaires distributed online to 130 respondents who have made decisions to purchase used cars. The lifestyle variable is measured through indicators of activities, interests, and opinions, while digital marketing is measured through accessibility, interactivity, entertainment, credibility, irritation, and information. Purchasing decisions are measured using indicators such as product conviction, purchasing habits, recommending to others, and repeat orders. Data analysis using multiple linear regression shows that both lifestyle and digital marketing significantly influence purchasing decisions. The results of the t-test and F-test reinforce these findings with significance values less than 0.05. These findings confirm that a marketing strategy that combines an understanding of consumer lifestyle and the utilization of digital platforms like Facebook can enhance consumer purchasing decisions in the used car business in Lampung.